Atom probe tomography of nitride semiconductors. (15th April 2018) - Rigutti, L.; Bonef, B.; Speck, J.; Tang, F.; Oliver, R.A.
Abstract: Atom probe tomography (APT) has emerged as a valuable tool in the study of nitride semiconductors, despite the challenges involved in achieving controlled field evaporation. In optoelectronics, it has provided insights into the nanostructure of light emitting diodes, laser diodes and microwires. In electronics, it has allowed insights into impurity doping and alloying effects in transistors. Coupled with direct correlative studies using other techniques and theoretical modelling based on the APT data, the availability of three dimensional compositional information on nitride heterostructures has had (and will continue to have) a profound impact on the design and development of devices. Graphical abstract: Image 1